Microbubbles and Nanobubbles with Ultrasound for Systemic Gene Delivery - Yoko Endo-Takahashi; Yoichi Negishi (MDPI AG, 2020)
The regulation of gene expression is a promising therapeutic approach for many intractable diseases. However, its use in clinical applications requires the efficient delivery of nucleic acids to target tissues, which is a major challenge. Recently, various delivery systems employing physical energy, such as ultrasound, magnetic force, electric force, and light, have been developed. Ultrasound-mediated delivery has particularly attracted interest due to its safety and low costs. Its delivery effects are also enhanced when combined with microbubbles or nanobubbles that entrap an ultrasound contrast gas. Furthermore, ultrasound-mediated nucleic acid delivery could be performed only in ultrasound exposed areas. In this review, we summarize the ultrasound-mediated nucleic acid systemic delivery system, using microbubbles or nanobubbles, and discuss its possibilities as a therapeutic tool.